The role of the sonographer – An investigation into the scope of practice for the sonographer internationally. Issue 1 (February 2022) - Miles, N.; Cowling, C.; Lawson, C.
Abstract: Introduction: There is global variance in the role of a practicing sonographer. Literature examining global sonographic roles and scope of practice is limited, despite the international applicability of ultrasound imaging. This study aimed to examine the common and divergent features of a practicing sonographer internationally, and their impact upon the development of a global standard of practice. Methods: An ethically approved mixed-methods online survey was conducted. The purposive sample included all 75 current elected council members of the ISRRT [International Society of Radiographers and Radiological Technologists], an international professional organisation. Results: Thirty-six individuals from at least 32 different countries responded, reflecting the sonography profession in all four ISRRT regions. The results suggest that sonographer education requirements differ widely, from on the job training (16%, 6/36) to undergraduate or postgraduate schooling (44%, 16/36). Registration and accreditation bodies were present in the jurisdiction of 41% (14/34) and 35% (12/33) of respondents respectively, though many were voluntary, physician-focused or non-specific to sonographers. Five of 11 (45%) respondents suggested that the sonographer–radiologist relationship is individual-dependent, and not primarily positive or negative. Ten of 28 (36%) suggested that other professionals do not know the role of the sonographer. Conclusion: The majority of ISRRT council member respondents believe that an international scope of practice could benefit and be implemented in their jurisdiction (26/28, 93% and 22/33, 67%). The key advantages noted were standardisation of education and improved professional mobility. However, lack of sonographer education and radiologist acceptance are important potential barriers. Implications for practice: An international scope of practice could be beneficial and implementable in most ISRRT jurisdictions. Professional mobility and education standardization are the primary advantages. Insufficient sonographer education and physician acceptance are the key potential obstacles.